Computational aero-acoustic modelling of external rear-view mirrors on a mid-sized Sedan. (February 2016) - Mukkamala, Yagnavalkya; Devabhaktuni, Sandeep; Rajkumar, Vishnu Ganesh
Ever-rising fuel costs necessitate design of fuel-efficient vehicles. Consequently, modern vehicle manufacturers are focused on designing low aerodynamic drag vehicles which would in-turn reduce the fuel consumption. This study analyses the contribution of external rear-view mirrors to the total drag force and the overall sound pressure level at the A, B and C pillars, while optimising the external rear-view mirror design accordingly. Solid Works renditions of external rear-view mirror models mounted on a reference luxury sedan were analysed using a commercially available computational fluid dynamic package ANSYS FLUENT. A different approach was followed to carry out the empirical flow visualisation and predict sound pressure levels. The aerodynamic characterisation of the vehicle was done utilising the widely used shear stress transport turbulence model, while the analysis of wind noise and the contributing vortices employed a large eddy simulation. This approach significantly reduced computational time without compromising on accuracy.